An introduction to the contemporary breeding of oil seed rape. Issue 11 (November 2013) - Wood, Tom; Teakle, Graham; Mackay, Ian
Abstract Plant breeding settled into its modern form a little over 100 years ago. Recent developments in genetics and genomics will not revolutionise this process but will increase the rate at which progress is made. Genetic manipulation could make great changes, though not in Europe until public opinion changes. Ironically, of all the methods used to introduce novel variation into crops, it is arguably the most benign.